Festa do encontro, festa dadivosa: a trezena franciscana na região rural de Tabocas em Abaeté/MG - Silva, Élen Ângela [UNESP] (2014)
This research is a result of the ethnography of St. Anthony of Tabocas party, realized in the region of Upper San Francisco, Minas Gerais. The festival is an event bounded directly to the families who lived and still live in rural areas of Abaeté and to the Franciscan devotion. The data collection was made possible through fieldwork in order to understand how are the religious practices of the revelers that celebrating the effectiveness of this miracle worker by trezena. This consists of thirteen days of celebration and prayer, containing tell one‟s beads, singing hymns and songs, celebration of the word and church masses that culminating in the so-called big party on 13th June, day of St. Anthony according to the Catholic calendar. The trezena singularized through his liturgical character, and, is above all, a moment of meeting those who migrated and who consider themselves far from their homeland. The thaumaturgic image of St. Anthony is celebrated by the action of the Franciscans that, for a long time, were present in the region. In this sense, the research presents part of the hagiography of St. Anthony and shows how the time of the party becomes moments of encounter, return to origins.